Mediation of functional gene and bacterial community profiles in the sediments of eutrophic Chaohu Lake by total nitrogen and season. (July 2019) - Fan, Yang-Yang; Li, Bing-Bing; Yang, Zong-Chuang; Cheng, Yuan-Yuan; Liu, Dong-Feng; Yu, Han-Qing
Abstract: Microbes in sediments contribute to nutrient release and play an important role in lake eutrophication. However, information about the profiles of functional genes and bacterial communities and the most important environmental factor affecting them in the sediments of eutrophic lake remains unrevealed. In this work, the real-time fluorescent quantitative polymerase chain reaction (qPCR) assay and 16S ribosomal RNA gene next generation sequencing analysis were used to explore the profiles of functional genes and bacterial communities in the sediments of Chaohu Lake. The selected 18 functional genes involved in C, N and P cycles were detected in most of samples. Seasonal variation and sediment variables were found to affect the profiles of functional genes and bacterial communities, and total nitrogen was the dominant environmental factor to drive the formation of bacterial community structure. Proteobacteria and Firmicutes were observed to be the two dominant phyla in the sediments with relative abundance ranging from 10.8% to 36.0% and 7.7%–46.7%, respectively. Three bacterial phyla, i.e., Actinobacteria, Proteobacteria, and Spirochaetes, were found to be significantly positively correlated with the C, N and P-cycle related functional genes. Bacterial community structure was the most important driver to shape the profiles of functional genes. Seasonal variation also influenced the co-occurrence patterns between functional genes and bacterial taxa as revealed by network analysis. The findings from this work facilitate a better understanding about the C, N, and P cycles in the sediments of eutrophic lakes. Graphical abstract: Image 1 Highlights: 18 functional genes involved in C, N and P cycles were detected in samples. Season affected the co-occurrence pattern between functional gene and bacterial taxa. TN was the most important factor to drive the formation of community structure. Profiles of functional genes were mainly mediated by bacterial communities. Abstract : The profiles of functional genes and bacterial communities in the sediments of Chaohu Lake were governed by total nitrogen and season.